Cohort fertility a case study of a Philippine community - Abeleda, Amparo Mariano 1941-
Changes in marriage and childbearing patterns can cause wide fluctuations in annual birth rates despite a constant average family size. One way to unfold these influences from one another is through an explicit longitudinal approach. Cohort analysis is such method. The present paper is an application of this method of study aimed at investigating changes in fertility trends in terms of timing patterns of successive generations of women differentiated according to their year of birth, age at marriage, education, work experience and annual family income.